Suicidal ideation modulates the reduction in serotonin transporter availability in male military conscripts with major depression: A 4-[18F]-ADAM PET study. (3rd October 2015) - Yeh, Yi-Wei; Ho, Pei-Shen; Chen, Chun-Yen; Kuo, Shin-Chang; Liang, Chih-Sung; Yen, Che-Hung; Huang, Chang-Chih; Shiue, Chyng-Yann; Huang, Wen-Sheng; Ma, Kuo-Hsing; Lu, Ru-Band; Huang, San-Yuan
Abstract : Objectives. Suicide is an important issue in the military service, since it can influence military morale and create dangerous situations for other personnel. The serotonin transporter (SERT) has been suggested to be involved in the pathophysiology of depression and suicidal behaviours. The aims of this study were to examine whether the brain SERT availability differs between military conscripts with depression and control subjects, and whether suicidal ideation is correlated with SERT availability. Methods. We used N, N -dimethyl-2-(2-amino-4-[ 18 F]-fluorophenylthio)benzylamine (4-[ 18 F]-ADAM) as a radioligand for positron emission tomography (PET) imaging. All participants completed the Hamilton Depression Rating Scale and Beck Scale for Suicide Ideation (BSS) prior to PET imaging. Results. The effect of major depression and BSS scores had an interaction on SERT availability. After adjusting for the BSS score, subjects with depression had lower SERT availability than control subjects ( F 1, 17 = 23.85, P < 0.001). A positive correlation between SERT availability and BSS scores was observed in the depression group ( F 1, 8 = 30.67, P = 0.001). The status of depression and intensity of suicidal ideation exert opposite effects on SERT availability. Conclusions. The extent of suicidal ideation may moderate the reduction effect in SERT binding observed in major depression in male military conscripts.